Mengoptimalkan Pendampingan Berbasis KKG dalam Upaya Meningkatkan Kompetensi Guru Kelas SD 29 Mataram dalam Penyusunan RPP - Salim, Agus (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2017)
This study aims to find out how far the effectiveness of the implementation of assistance in improving the competence of teachers SD Negeri 29 Mataram in the preparation of Learning Implementation Plan (RPP) based on the character education of the nation beneficial for teachers in improving professionalism of teachers in daily tasks. In the implementation of School Action Research (PTS) is done as much as two cycles, where each cycle there are four stages of planning, implementation, observation and reflection. The indicator of success in this research is Civics Teacher Competence is: if 85% of the number of mentors have reached the average value ≥ 85.00. School Action Research Results (PTS) in cycle II obtained data as follows; 1) Principal observation (4.20), 2) teacher observation (4.00), 3) Individual work (86.66) and 4) percentage of mastery (100%,). The success indicator has exceeded the School Action Research (PTS) was declared successful, and the research was stopped in cycle II. Group guidance is very effective in improving teacher competence in the preparation of character education-based RPP because 100% of total participants as many as 6 (six) teachers have succeeded in preparing the RPP based on character education as expected. It is suggested to the Principals of Colleagues to conduct mentoring activities for teachers who are the responsibility in an effort to improve the competence of teachers in the actual learning activities in the classroom.